Phytochemical and Antioxidant Assay of Tabebuia aurea Stem Extract: A Potential Source of Bioactive Compounds - Al Akbar, Fadhlur Rohman; Kurniawan, Rahmat (Journal of Science and Applicative Technology, 2025)
Tabebuia aurea has been recognized for its traditional medicinal applications and promising antioxidant properties. The research addresses a gap in understanding the phytochemical and antioxidant characteristics of T. aurea in Indonesia. This study aims to conduct phytochemical screening and evaluate the antioxidant activity of T. aurea stem extracts. The stems of T. aurea were collected from the Botanical Garden of the Sumatra Institute of Technology and authenticated at the Bogoriense-BRIN Herbarium in Bogor to ensure the accuracy of the plant species. The samples were cleaned and dried indoors to prevent the degradation of active compounds before being ground into fine simplicia powder. The extraction process was carried out through maceration utilizing different solvents, including methanol, aquadest, ethyl acetate, and n-hexane. Phytochemical analysis revealed the presence of tannins in the methanol extract. The aquadest extract contains tannins, terpenoids, and flavonoids. Phytochemical screening indicated that the ethyl acetate extract comprises alkaloids and flavonoids, while the n-hexane extract contains alkaloids and saponins. An antioxidant assay using the DPPH method shows that T. aurea stem extracts exhibit a significant ability to scavenge free radicals. Methanol extract has IC50 value of 51.24 μg/mL (strong), aquadest extract has IC50 of 65.34 μg/mL (strong), ethyl acetate extract has IC50 of 79.88 μg/mL (strong), and n-hexane extract has IC50 of 256.73 μg/mL (very weak). For comparison, the vitamin C control has an IC50 of 43.95 μg/mL (very strong). The findings of this study demonstrate that the extract from the stem of Tabebuia aurea contains bioactive compounds with potential as a natural antioxidant source. This antioxidant property highlights the potential of T. aurea stem as a valuable raw material for developing health and cosmetic products that leverage its antioxidant capabilities.